Determination of the integrated luminosity at HERA using elastic QED compton events - Aaron, Francisc Dionisie; Hennekemper, Eva; Krüger, Katja; Lendermann, Victor; Pirumov, Hayk; Sauter, Michel David; Schöning, André; Schultz-Coulon, Hans-Christian (The European physical journal. C, Particles and fields, 2012)
A measurement of the integrated luminosity at the ep collider HERA is presented, exploiting the elastic QED Compton process ep→eγp. The electron and the photon are detected in the backward calorimeter of the H1 experiment. The integrated luminosity of the data recorded in 2003 to 2007 is determined with a precision of 2.3 %. The measurement is found to be compatible with the corresponding result obtained using the Bethe-Heitler process.